DESIGN AND ANALYSIS OF SLOT LOADED RECTANGULAR PATCH ANTENNA FOR WIRELESS COMMUNICATION SYSTEM - Mr. Prakash S. Andhare (International Journal of Innovations in Engineering Research and Technology, 2021)
A multiple-input multiple-output (MIMO) technique has been considered one of the most promising technologies to enhance the performance of wireless communication systems with high-speed transmission rates. A MIMO system utilizing several antenna components is more advantageous than a single-input single-output (SISO) system in terms of increasing channel capacity and reducing transmitting power. Conventional universal serial bus (USB) dongles are attractive for providing plug and- play functionality in mobile communication devices such as laptops. Future wireless USB dongles should be capable of accommodating higher data rates than the current systems owing to the advent of various multimedia services. Up to date, most MIMO antenna systems with more than two antennas are three-dimensional rather than planar. However, the basic problem with the MIMO systems is the requirement of electrically small antennas which usually have several constraints. Hence, these antennas are considered in our project work.